2014
DOI: 10.1371/journal.pone.0106026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Risk Factors Associated with Anti-Epileptic Drug Responsiveness in Canine Epilepsy

Abstract: The nature and occurrence of remission, and conversely, pharmacoresistance following epilepsy treatment is still not fully understood in human or veterinary medicine. As such, predicting which patients will have good or poor treatment outcomes is imprecise, impeding patient management. In the present study, we use a naturally occurring animal model of pharmacoresistant epilepsy to investigate clinical risk factors associated with treatment outcome. Dogs with idiopathic epilepsy, for which no underlying cause w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 50 publications
3
72
0
5
Order By: Relevance
“…The temporal distribution of epileptic seizures is an important prognostic factor in IE, with dogs experiencing CS less likely to achieve remission (Packer et al, 2014), experiencing a decreased survival time (Arrol et al, 2012;Berendt et al, 2007;Monteiro et al, 2012;Saito et al, 2001) and an increased likelihood of euthanasia (Fredso et al, 2014) compared to dogs with single epileptic seizure episodes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal distribution of epileptic seizures is an important prognostic factor in IE, with dogs experiencing CS less likely to achieve remission (Packer et al, 2014), experiencing a decreased survival time (Arrol et al, 2012;Berendt et al, 2007;Monteiro et al, 2012;Saito et al, 2001) and an increased likelihood of euthanasia (Fredso et al, 2014) compared to dogs with single epileptic seizure episodes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…(Patterson, 2014;Thomas, 2010), and status epilepticus (SE) as either (a) one continuous seizure lasting for more than 10 minutes without gaining consciousness (for generalized convulsive seizures) (Packer et al, 2014) or (b) two or more discrete epileptic seizures between which there is incomplete recovery of consciousness (Berendt et al, 2015). Seizure activity lasting less than 10 min without gaining Cross breeds (n=23), GSDs (n=22), Border Collies (n=21) and Labrador Retrievers (n=13).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Finding an effective AED that reduces seizure frequency to an acceptable level (generally classed as more than 50 per cent reduction in veterinary medicine), or results in remission (seizure-freedom) can be a long process, with several AEDs trialled before optimum treatment is reached (Packer and others 2014). With more AEDs becoming available to veterinary patients, knowing whether (and when) to include further therapies can be challenging for practitioners, when faced with the balance between seizure control and side effect profiles.…”
mentioning
confidence: 99%
“…The same study found that only dogs that responded to the first AED became seizure-free. Lastly, Packer et al (2014) found that the presence of cluster seizures and thus seizure density is a more influential risk factor on the likelihood of achieving remission in canine epilepsy than seizure frequency or the total number of seizures prior to treatment.…”
Section: Primidone Vs Imepitoinmentioning
confidence: 95%